Schistosoma mansoni Larval Extracellular Vesicle protein 1 (SmLEV1) is an immunogenic antigen found in EVs released from pre-acetabular glands of invading cercariae - Gilda Padalino (PLOS Neglected Tropical Diseases, 2021)
Extracellular Vesicles (EVs) are an integral component of cellular/organismal communication and have been found in the excreted/secreted (ES) products of both protozoan and metazoan parasites. Within the blood fluke schistosomes, EVs have been isolated from egg, schistosomula, and adult lifecycle stages. However, the role(s) that EVs have in shaping aspects of parasite biology and/or manipulating host interactions is poorly defined. Herein, we characterise the most abundant EV-enriched protein in Schistosoma mansoni tissue-migrating schistosomula (Schistosoma mansoni Larval Extracellular Vesicle protein 1 (SmLEV1)). Comparative sequence analysis demonstrates that lev1 orthologs are found in all published Schistosoma genomes, yet homologs are not found outside of the Schistosomatidae. Lifecycle expression analyses collectively reveal that smlev1 transcription peaks in cercariae, is male biased in adults, and is processed by alternative splicing in intra-mammalian lifecycle stages. Immunohistochemistry of cercariae using a polyclonal anti-recombinant SmLEV1 antiserum localises this protein to the pre-acetabular gland, with some disperse localisation to the surface of the parasite. S. mansoni—infected Ugandan fishermen exhibit a strong IgG1 response against SmLEV1 (dropping significantly after praziquantel treatment), with 11% of the cohort exhibiting an IgE response and minimal levels of detectable antigen-specific IgG4. Furthermore, mice vaccinated with rSmLEV1 show a slightly reduced parasite burden upon challenge infection and significantly reduced granuloma volumes, compared with control animals. Collectively, these results describe SmLEV1 as a Schistosomatidae-specific, EV-enriched immunogen. Further investigations are now necessary to uncover the full extent of SmLEV1’s role in shaping schistosome EV function and definitive host relationships.